Cardiovascular effects of approved drugs for rheumatoid arthritis - Atzeni, Fabiola; Rodríguez-Carrio, Javier; Popa, Călin D; Nurmohamed, Michael T; Szűcs, Gabriella; Szekanecz, Zoltán (Nature reviews. Rheumatology, 2021)
The risk of cardiovascular disease is increased in patients with rheumatoid arthritis compared with the general population owing to the influence of traditional and non-traditional risk factors. Inflammation has a pivotal contribution and can accelerate the atherosclerotic process. Although dampening inflammation with DMARDs should theoretically abrogate this process, evidence suggests that these drugs can also promote atherosclerosis directly and indirectly, hence adding to an increased cardiovascular burden. However, the extent and direction of the effects largely differ across drugs. Understanding how these drugs influence endothelial damage and vascular repair mechanisms is key to understanding these outcomes. NSAIDs and glucocorticoids can increase the cardiovascular risk. Conversely, conventional, biologic and targeted DMARDs control inflammation and reduce this risk, although some of these drugs can also aggravate traditional factors or thrombotic events. Given these data, the fundamental objective for clinicians should be disease control, in an individualized approach that considers the most appropriate drug for each patient, taking into account joint and cardiovascular outcomes. This Review provides a comprehensive analysis of the effects of DMARDs and other approved drugs on cardiovascular involvement in rheumatoid arthritis, from a clinical and mechanistic perspective, with a roadmap to inform the research agenda.